2011
DOI: 10.1007/s11205-011-9844-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Multilevel Constructs: Validation Methods and Empirical Findings for the EDI

Abstract: Multilevel, Construct validation, School readiness,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…The reliability and validity of these data sources have been well documented. [16][17][18][19] Study cohorts Using hospital and physician claims data from 1 April 1984 to 31 March 2012 along with prescription claims from 1 April 1996, we identified all Manitobans with MS using a case definition that was previously validated against medical records. 20 These were individuals with ≥3 records related to MS in any combination of hospital, physician, or prescription claims.…”
Section: Methodsmentioning
confidence: 99%
“…The reliability and validity of these data sources have been well documented. [16][17][18][19] Study cohorts Using hospital and physician claims data from 1 April 1984 to 31 March 2012 along with prescription claims from 1 April 1996, we identified all Manitobans with MS using a case definition that was previously validated against medical records. 20 These were individuals with ≥3 records related to MS in any combination of hospital, physician, or prescription claims.…”
Section: Methodsmentioning
confidence: 99%
“…When test scores are interpreted at the individual level, construct validity evidence is obtained at the individual level. When data from multilevel measures are reported, interpreted, and used at a group level (e.g., at the level of school, neighbourhood, country), construct validity evidence also needs to reflect this same group level of data Forer and Zumbo 2011). As with all measures, it is important for an array of empirical evidence to be compiled and a compelling argument put forward to support the intended inference(s) and to show that alternative or competing inferences are not more viable.…”
Section: Validation Of Individual Differences Versus Multilevel Constmentioning
confidence: 99%
“…Such evidence might include (multilevel) reliability, content-related evidence, (multilevel) factor structure, substantive processes, (multilevel) external relationships, articulation of values (e.g., in theory, the construct, score meaning, and use), and both intended social and personal consequences and unintended social and personal side effects of legitimate test use on the meaning of test scores. Forer and Zumbo (2011) describe multilevel construct validity and provide some conceptual and technical psychometric validity evidence for the EDI. Linn (2008 challenged us to think about the potential errors in inference that can be made across levels of datathat is, what Zumbo and Forer refer to as ecological or atomistic fallacies of measurement data inferences.…”
Section: Validation Of Individual Differences Versus Multilevel Constmentioning
confidence: 99%
“…A growing number of studies have established that the EDI has good internal and test-retest reliability as well as external validity (Forget-Dubois et al 2007;Janus and Offord 2007;Forer and Zumbo 2011;Guhn and Goelman 2011;Hymel, Le Mare, and McKee 2011;Janus, Brinkman, and Duku 2011). Early studies of the instrument indicated that: 'The EDI's psychometric properties have proven to be acceptable' (Janus and Offord 2007, 18;).…”
Section: Outcome Variablesmentioning
confidence: 99%